Condition and Management Strategy of Coral Ecosystem in Kedindingan Island, Bontang City - Samin, Andriyanto; Mustakim, Mustakim; Fitryana, Fitryana; Suyatna, Iwan; Nikhlani, Andi; Ningsih, Etik Susilowati (Torani Journal of Fisheries and Marine Science, 2023)
Kedindingan Island is one of the Marine Conservation areas in East Kalimantan Province with rich natural resource. This study aims to determine the extent of coral distribution and health, determine the health condition of live coral cover and to formulate management strategies in Kedindingan Island for the realization of sustainable coral management. The results of the analysis using Landsat 8 imagery showed live coral was 55.44 Ha in 2015 and 48.06 Ha in 2022. Love coral cover in stations 1,2, and 4 were in good category i.e. 52,53$, 53,6%, and 60,34%, respectively . whilst in station 3  31,34% was moderate category. There are three priority management strategies for coral ecosystem management in Kedindingan Island, the first is to create a team in each region consisting of policy makers, academics, and the community, the second is to increase the role of NGOs and local communities in monitoring and supervising coral ecosystems, and the third is to improve management and develop rehabilitation methods and monitor corals regularly in Kedindingan Island.